2016
DOI: 10.3389/fpsyt.2016.00178
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of the 12-Item Center for Epidemiologic Studies Depression Scale among Blacks and Whites

Abstract: BackgroundThe Center for Epidemiologic Studies Depression (CES-D) scale is one of the most widely used tools to measure depressive symptoms in epidemiological studies. Given the importance of cross-racial measurement equivalence of the CES-D scale for research, we performed confirmatory factor analysis (CFA) of the 12-item CES-D in a nationally representative sample of Black and White adults in the United States.MethodsWe used data from the National Survey of American Life (NSAL), 2001–2003. A total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
4
21
0
Order By: Relevance
“…Our findings can be explained by the literature on ethnic differences in the degree to which mental disorders are somaticized [ 32 ]. Non-White ethnic groups such as Hispanics [ 32 ], African Americans [ 44 ], and East Asians [ 33 ] may have a higher tendency for somatization of mental health symptoms than non-Hispanic Whites. Studies have shown that women in general [ 32 ], and ethnic minority women in particular [ 45 , 46 , 47 ], have a high tendency for somatization of psychiatric disorders such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings can be explained by the literature on ethnic differences in the degree to which mental disorders are somaticized [ 32 ]. Non-White ethnic groups such as Hispanics [ 32 ], African Americans [ 44 ], and East Asians [ 33 ] may have a higher tendency for somatization of mental health symptoms than non-Hispanic Whites. Studies have shown that women in general [ 32 ], and ethnic minority women in particular [ 45 , 46 , 47 ], have a high tendency for somatization of psychiatric disorders such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed worse item loadings for positive items, namely “as good” and “hopeful,” in Blacks than Whites. In the final model with a very good fit to the data, the item “as good” showed poor loading for Whites and Blacks, however, the item “hopeful” showed good loading for Whites but poor loading for Blacks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not race alters simultaneous experience and presentation of positive and negative affect is still unknown [ 29 , 30 ]. While some studies have suggested that the factorial structure of depression scales is invariant across racial groups [ 39 , 40 , 41 ], other studies have shown that the degree by which positive and negative affect correlate may depend on race and ethnicity [ 29 , 42 , 43 ]. While there is an ongoing debate whether or not positive and negative affect similarly represent depression among Whites and Blacks [ 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], there are studies showing higher reliability of negative affect despite lower reliability of depression measures for Blacks compared to Whites [ 40 , 41 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response items ranged from (0) rarely or none of the time to (3) most of the time, with a sum score potentially ranging from 0 to 24. The full and modified version of the CES-D are valid in African Americans [ 26 , 27 , 28 ] (Cronbach’s alpha = 0.76).…”
Section: Methodsmentioning
confidence: 99%